Sex Differences in the Association between Night Shift Work and the Risk of Cancers: A Meta-Analysis of 57 Articles. (26th November 2018) - Liu, Wen; Zhou, Zhonghan; Dong, Dahai; Sun, Lijiang; Zhang, Guiming
Abstract : Objectives . To identify the association between night shift work and the risk of various cancers with a comprehensive perspective and to explore sex differences in this association. Methods . We searched PubMed, Embase, and Web of Science for studies on the effect of night shift work on cancer, including case-control, cohort, and nested case-control studies. We computed risk estimates with 95% confidence intervals (CIs) in a random or fixed effects model and quantified heterogeneity using theI 2 statistic. Subgroup, metaregression, and sensitivity analyses were performed to explore potential sources of heterogeneity. Contour-enhanced funnel plots and the trim and fill method were used together to analyze bias. Linear dose–response analysis was used to quantitatively estimate the accumulative effect of night shift work on the risk of cancer. Results . Fifty-eight studies were eligible for our meta-analysis, including 5, 143, 838 participants. In the random effects model, the pooled odds ratio (OR) of cancers was 1.15 (95% CI = 1.08–1.22, P < 0.001 ;I 2 = 76.2 % ). Night shift work increased the cancer risk in both men (OR = 1.14, 95% CI = 1.05–1.25, P = 0.003 ) and women (OR = 1.12, 95% CI = 1.04–1.20, P = 0.002 ). Subgroup analyses showed that night shift work positively increased the risk of breast (OR = 1.22, 95% CI = 1.08–1.38), prostate (OR = 1.26, 95% CI = 1.05–1.52), and digestive system (OR = 1.15, 95% CI = 1.01–1.32) cancers. For every 5 years of night shift work, the cancer risk increased by 3.2% (OR = 1.032, 95% CI = 1.013–1.051). Conclusion . This is the first meta-analysis identifying the positive association between night shift work and the risk of cancer and verifying that there is no sex difference in the effect of night shift work on cancer risk. Cancer risk increases with cumulative years of night shift work.